Narrative Communication and Sustainability Perception: How Eco-Conscious European Consumers interpret Illipe Butter - Hillary Tasya Medina; Aditya Nugroho Pratomo; Dhita Widya Putri (Program Studi Ilmu Komunikasi Fakultas Ilmu Sosial Dan Ilmu Politik Universitas Bandar Lam, 2026)
This study analyzes how eco-oriented European consumers evaluate sustainability narratives about illipe butter, a natural product marketed as a sustainable ingredient from Borneo, Indonesia. This study draws on green consumer behaviour, narrative persuasion, and the economics of communication sustainability to develop a risk-signalling framework. Semi-structured interviews were conducted with 12 eco-conscious consumers in Europe, and the data were analysed reflexively using thematic analysis. It was found that credibility and the availability of verifiable evidence emerged as threshold conditions shaping whether sustainability narratives were accepted or rejected. Furthermore, without credibility, emotional appeal alone is insufficient. Respondents perceived functional benefit framing to anchor sustainability claims in tangible product performance, thereby enhancing perceived value. Thus, the counterbalanced emotional appeal resulted in the most favourable responses when sustainability claims were framed in a functionally beneficial manner. This research connects the risk-value narrative with mechanisms within sustainable communication.